ANALYSIS OF THE FULFILLMENT OF AVIATION SECURITY FACILITIES IN THE OPERATION OF THE REGIONAL GOVERNMENT VIP BUILDING AT EL TARI KUPANG AIRPORT - Abhellya Christine, Gracyel; Suprapto, Yuyun Suprapto; Fatmawati (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
Aviation security is a crucial aspect of airport operations. The condition of the El Tari Kupang Airport RegionalGovernment VIP building, which has direct access to the apron area, and the lack of aviation security facilities can pose risks to aviation safety and security. This research used a quantitative approach with a cross-sectional study design. The research method employed the Gap Analysis Checklist and the Analytical Hierarchy Process (AHP). The AHP method was used to determine the priority of mandatory security facilities, while the gap analysis method was used to measure the level of compliance of existing facilities with Regulation KM 39 of 2024. The results of the research indicate that the level of compliance is still low. Of all the indicators regulated, only four aspects meet the standards, namely Hand Held Metal Detectors (HHMD), warning systems to mobile phones or management rooms, manual cabin baggage inspection tables, and communication devices with security unit management. Meanwhile, the AHP analysis identified the security facilities that should be available in the regionalgovernment VIP building based on the order of eigenvector values: CCTV in the inspection area (0.1569), security facility testing equipment (0.1420), a multi-view cabin X-ray machine with active TIP functionality (0.1363), Walk Through Metal Detector (WTMD) (0.1327), and Hand Held Metal Detector (HHMD) (0.1087). This situation poses a serious potential risk to aviation safety. Although the probability of the risk occurring is relatively low, the impact is very high, so immediate mitigation efforts are needed through the improvement of facilities and security procedures in the regionalgovernment VIP building.